Processamento e caracterização de ligas amorfizáveis TiCuNiZr e TiFeCoZr - Medeiros, Bruno Bellini (2010)
Searching the development of bulk metallic glasses the research takes two directions, the development of alloys with a high glass forming ability and development of new processes or improving existing processes. In this context, the present study aimed at to evaluate the solidification processes suction and centrifugal casting, both using copper moulds. The alloys Ti34Cu36Ni8Zr22 and (TiZr)80Co12Fe8 were investigated. Fully amorphous melt spun ribbons were produced presenting good thermal parameters. However, the production of bulky samples by the foregoing processes showed that the alloys have low glass forming ability. The centrifugal casting process, despite the high cooling rate have failed to keep the chemical composition, presented turbulent filling and was unable to prevent heterogeneities that are carried from the crucible into the sample. The suction process showed high cooling rate with a good combination of appropriate mould filling, maintenance of chemical composition and to avoid the presence of heterogeneities in a satisfactory manner. Both processes kept the oxygen level at satisfactory values, below 1000 ppm. Comparing with the arc melting process using copper crucible, the suction casting process decreased slightly, in average, the oxygen levels. On the other hand, the centrifugal casting process increased slightly the contamination by oxygen.